2018
DOI: 10.4193/rhinol/18.027
|View full text |Cite
|
Sign up to set email alerts
|

Training in ENT; a comprehensive review of existing evidence

Abstract: Despite an expansion of fellowship opportunities over the last three decades, there is still incomplete regulation and standardisation of fellowship training. The aim of this comprehensive review was to examine existing evidence about the ear, nose and throat (ENT) training, especially focused on surgical and non-surgical aspects of the training. It is challenging to critically evaluate and compare training programmes across nations for several reasons. Studies on the subject rely entirely on trainee self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…To this end, the efficacy of these novel educational tools was examined in a comprehensive systematic review which shows e-learning to be a powerful alternative to standard teaching techniques within otolaryngology education, for both residents and medical students. Of the 12 studies included within this review, nine reported either improved objective performance in academic or clinical measures, or no difference in performance but higher satisfaction with use of elearning [6,44]. However, technical skill was not assessed in these studies and, though this type of improvement has been demonstrated in other specialties, such a benefit has not been demonstrated in ENT [44].…”
Section: The Role Of E-learning In Simulation Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the efficacy of these novel educational tools was examined in a comprehensive systematic review which shows e-learning to be a powerful alternative to standard teaching techniques within otolaryngology education, for both residents and medical students. Of the 12 studies included within this review, nine reported either improved objective performance in academic or clinical measures, or no difference in performance but higher satisfaction with use of elearning [6,44]. However, technical skill was not assessed in these studies and, though this type of improvement has been demonstrated in other specialties, such a benefit has not been demonstrated in ENT [44].…”
Section: The Role Of E-learning In Simulation Trainingmentioning
confidence: 99%
“…Web learning in medical education has become increasingly popular due to its advantages over traditional teaching methods such as flexible scheduling, reduced costs and individualised instruction [6]. In surgical specialties, elearning includes the use of virtual patient cases, digital modelling and online tutorials [35].…”
Section: The Role Of E-learning In Simulation Trainingmentioning
confidence: 99%
“…In the United States, otolaryngic allergy education, including didactics and hands-on training, during ORL residency, has been mandated by the American Board of Otolaryngology and the Postgraduate Medical Education Accreditation Council ( 4 ). Also, the logbook, prepared by The European Union of Medical Specialist (UEMS) ORL Section, to provide standardization in ORL training programs in pan-Europe, aims to ensure ORL residents with the skills of allergy practice ( 5 ). Turkey is also a member of the Confederation of European Otorhinolaryngology-Head and Neck Surgery (ORL-HNS).…”
Section: Introductionmentioning
confidence: 99%